Eastern Christianity and the Cold War : 1945 - 91 - Leuştean, Lucian 1967- (Routledge studies in the history of Russia and Eastern Europe;, 2010)
This text provides a comprehensive overview of the dynamics between Eastern Christianity and politics from the end of the Second World War to the fall of communism, covering all the orthodox churches, both inside the communist bloc and outside it, including diasporic churches in Africa, Asia, America and Australia.